2019
DOI: 10.1021/jacs.9b00440
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function in Antimicrobial Piscidins: Histidine Position, Directionality of Membrane Insertion, and pH-Dependent Permeabilization

Abstract: Piscidins are histidine-enriched antimicrobial peptides that interact with lipid bilayers as amphipathic α-helices. Their activity at acidic and basic pH in vivo makes them promising templates for biomedical applications. This study focuses on p1 and p3, both 22-residue-long piscidins with 68% sequence identity. They share three histidines (H3, H4 and H11) but p1, which is significantly more permeabilizing, has a fourth histidine (H17). This study investigates how variations in amphipathic character associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
107
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(123 citation statements)
references
References 122 publications
(282 reference statements)
12
107
4
Order By: Relevance
“…The most N-terminal Arg residue, Arg5, could become static because the N-terminal His-tag present in ChiZ-FL (but absent in ChiZ1-64) might attach to the membrane. 21 That still leaves two RP residues, Arg34 and Arg39, in the midsection unaccounted for. As the data from the next experiment indicate, even in the ChiZ1-64 construct, these two residues, along with other midsection Arg residues, interact with lipids, and the resulting loss in dynamics potentially prevented their detection by INEPT, but the loss in dynamics was incomplete so Arg34 and Arg39 were not detectable by CP either.…”
Section: Resultsmentioning
confidence: 99%
“…The most N-terminal Arg residue, Arg5, could become static because the N-terminal His-tag present in ChiZ-FL (but absent in ChiZ1-64) might attach to the membrane. 21 That still leaves two RP residues, Arg34 and Arg39, in the midsection unaccounted for. As the data from the next experiment indicate, even in the ChiZ1-64 construct, these two residues, along with other midsection Arg residues, interact with lipids, and the resulting loss in dynamics potentially prevented their detection by INEPT, but the loss in dynamics was incomplete so Arg34 and Arg39 were not detectable by CP either.…”
Section: Resultsmentioning
confidence: 99%
“…The amphipathic α-helical secondary structure presented by several AMPs is crucial for peptide activity. Some reports already explored piscidin conformation and activity, as well as their mode of action on pathogen membranes, using artificial membranes that mimic the natural ones and can elucidate the mechanisms underlying the effects observed on pathogenic cells [47][48][49]. In addition, Schiffer-Edmundson helical wheel diagrams are often used to predict the hydrophobic and hydrophilic regions in the secondary structure of these peptides.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that after exposure to 500 nM NEC220, which deposited NEC220 on the membrane surface at high density (molar ratio protein/lipid (P/L) = 1/45), the membrane thickened by 0.49 ± 0.17 Å (68% confidence interval), in the context of the orientation model (Table S1). Thinning of membranes tethered to flat substrates has been observed with proteins that generate positive curvature by inserting into the headgroup region (Chen et al, 2003;Mihailescu et al, 2014;Mihailescu et al, 2019). This is because forcing the headgroups apart on a flat substrate increases the area per lipid and thins the membrane (the hydrophobic tails form a constant-volume cylinder, the height of which must decrease if the area is increased).…”
Section: Soluble Nec Inserts Peripherally Into the Tethered Lipid Bilayersmentioning
confidence: 99%